Vehicle thermal microclimate evaluation during Brazilian summer broiler transport and the occurrence of PSE (Pale, Soft, Exudative) meat - Simões,Gislaine Silveira (2009)
The formation of a thermal microclimate within the vehicle during the transport of broilers from farm to slaughterhouse affects the birds' welfare and potentially promotes the development of PSE meat. Thus, the aim of this work was to evaluate the effects of routine commercial practices on the vehicle microclimate formed during transportation of broilers. Twenty-four hours postmortem Pectoralis major m. samples were classified as PSE meat by determining pH and color (L*, a* e b*). Results showed that broiler located at the rear of the truck and with longer journey presented higher amounts of PSE meat because birds were under harsh conditions of both temperature and relative humidity. The ventilation decreased gradually from the front to the rear of the truck, and the water bath at the farm was beneficial over a long distance by reducing the overall occurrence of PSE meat.